Topological Electronics: Signatures of a Charge Density Wave Phase and the Chiral Anomaly in the Fermionic Material Cobalt Monosilicide CoSi (Adv. Electron. Mater. 2/2020). (13th February 2020) - Schnatmann, Lauritz; Geishendorf, Kevin; Lammel, Michaela; Damm, Christine; Novikov, Sergey; Thomas, Andy; Burkov, Alexander; Reith, Heiko; Nielsch, Kornelius; Schierning, Gabi
Abstract : The framework model of an interplay between charge density waves and topological transport features is investigated in terms of electrical transport by Gabi Schierning and co‐workers in article number 1900857 . Single‐crystalline ribbons of cobalt silicide are prepared from bulk and characterized. Their electrical transport is analyzed using a semiclassical model for quantum transport. Features of charge density wave phases in combination with chiral anomaly are investigated.